Analisis Kepuasan dan Loyalitas Pelanggan Hotel Berbintang Menggunakan SEM-PLS: Bukti Empiris dari Jakarta Barat: Analysis of Customer Satisfaction and Loyalty of Star-Rated Hotels Using SEM-PLS: Empirical Evidence from West Jakarta - Susanto, Taufik; Lusinto, Widodo Hari; Gustini, Tin (OGZ Research & Publishing, 2026)
Objective : This study aims to analyze the influence of service personalization, communication effectiveness, and loyalty programs on customer satisfaction and loyalty at star-rated hotels in West Jakarta. Methodology : The study used a quantitative approach with an explanatory design. Data were collected through a survey using a structured questionnaire to 96 respondents selected by purposive sampling. Data analysis was performed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). Research results : The results showed that communication effectiveness and loyalty programs have a positive and significant effect on customer satisfaction and loyalty, while service personalization did not show a significant effect. Customer satisfaction was shown to act as a mediating variable that strengthens loyalty. These findings emphasize the importance of effective communication strategies and loyalty programs in improving hotel competitiveness.